Eskebornite CuFeSe2: Solid-State Synthesis and Thermoelectric Properties - Se-Hyeon Choi; Il-Ho Kim (Inorganics)
Eskebornite (CuFeSe2), a member of the I–III–VI2 ternary semiconductor family, was explored in this study as a potential thermoelectric material, offering new insights into its synthesis, structural characteristics, and transport behavior. Structurally analogous to chalcopyrite (CuFeS2)—an extensively studied antiferromagnetic semiconductor—eskebornite remains relatively underexplored, particularly regarding its solid-state synthesis and thermoelectric performance. To address this gap, pure eskebornite was synthesized via mechanical alloying followed by hot pressing, a method that enables the fine control of its phase composition and microstructural features. The synthesized undoped CuFeSe2 exhibited p-type nondegenerate semiconducting behavior, with electrical conductivity increasing monotonically over the temperature range of 323–623 K, indicative of thermally activated carrier transport. Simultaneously, a decreasing trend in thermal conductivity with temperature was observed, likely resulting from intensified phonon scattering, which serves to suppress heat transport and enhance the thermoelectric efficiency by maintaining a thermal gradient across the material. A peak in the Seebeck coefficient occurred between 473 and 523 K, suggesting the onset of intrinsic carrier excitation and a transition in dominant carrier transport mechanisms. The material exhibited a maximum power factor of 1.55 μWm−1K−2, while the dimensionless thermoelectric figure of merit (ZT) reached a peak value of 0.37 × 10−3 at 523 K. Although the ZT remains low, these results underscore the potential of eskebornite as a thermoelectric candidate, with substantial room for optimization through chemical doping, microstructural engineering, or nanostructuring approaches to enhance the carrier mobility and reduce the lattice thermal conductivity.